PELATIHAN ECO-ENZYME BAGI KELOMPOK WANI TANI MAWAR BODAS KOTA TASIKMALAYA - Waliyyan, Azka; Nursifah, Fitri; Alvan, Eri Nur; Khasanah, Rokhayatun; Anggriani, Mita; Nurmaulida, Astrid (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
From the past until now, waste in Indonesia has become a problem that has not been resolved, in the City of Tasikmalaya with 10 Districts it produces 313,956.3 kg/day of waste per day, with the dominant composition of waste being organic waste originating from food waste or household waste. 48%, various efforts were made to reduce waste problems including turning organic waste into liquid organic fertilizer (POC) through eco-enyzm training. The purpose of this community service is as a stimulus for the community, especially the Mawar Bodas Women Farmer Group, Kahuripan Village, Tawang District, Tasikmalaya City to be aware of the importance of managing organic waste and turning it into liquid organic fertilizer. The method used in community service is demonstration, where the resource person explains the material and puts it into practice. The result of this community service is that people understand and are aware of organic waste management.